2006
DOI: 10.2193/0022-541x(2006)70[1735:shrifm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sciurid Habitat Relationships in Forests Managed Under Selection and Shelterwood Silviculture in Ontario

Abstract: Although partial forest harvesting is practiced over large areas, managers know little about its impacts on sciurid rodents, particularly on northern (Glaucomys sabrinus) and southern flying squirrels (G. volans) in the northeastern United States and Canada. We examined habitat relationships of sciurid rodents (northern flying squirrels, southern flying squirrels, red squirrels [Tamiasciurus hudsonicus], and eastern chipmunks [Tamias striatus]) at 2 spatial scales in managed and unmanaged coniferous and hardwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 34 publications
5
56
0
Order By: Relevance
“…In central Ontario, Holloway and Malcolm (2006) found that densities of large-diameter live and dead trees were important predictors of red squirrel and northern flying squirrel abundance, and that both species were less abundant in white pine stands that recently experienced a shelterwood harvest. In the boreal forest, red squirrel abundance was found to be low in harvested black spruce stands with 25% residual structure, but comparable to mature forest in stands with 50% residual structure (Lawrence 1996).…”
Section: Rodentsmentioning
confidence: 99%
“…In central Ontario, Holloway and Malcolm (2006) found that densities of large-diameter live and dead trees were important predictors of red squirrel and northern flying squirrel abundance, and that both species were less abundant in white pine stands that recently experienced a shelterwood harvest. In the boreal forest, red squirrel abundance was found to be low in harvested black spruce stands with 25% residual structure, but comparable to mature forest in stands with 50% residual structure (Lawrence 1996).…”
Section: Rodentsmentioning
confidence: 99%
“…Smith 1968;C.C. Smith 1968), but are also found in conifer-hardwood mixtures and pure hardwood forests (Kemp and Keith 1970;Rusch and Reeder 1978;Holloway and Malcolm 2006). Population fluctuations of holarctic tree squirrels (Tamiasciurus and Sciurus) have been related to availability of seed crops of coniferous trees (M.C.…”
Section: Introductionmentioning
confidence: 99%
“…The northern flying squirrel and the red squirrel typically inhabit coniferous forests (Goheen and Swihart 2005;Holloway and Malcolm 2006). In this study, our sampling was limited to mature deciduous forest types.…”
Section: Discussionmentioning
confidence: 99%